Phantoms of the deep - The Discovery Channel (USA : The Discovery Channel, 2000)
Beyond the colorful coral reefs and far beneath the crashing waves, is a dark, mysterious world teeming with monstrosities unlike any mankind has ever imagined. This strange, alien world of real life sea monsters is a realm where time seems to have stood still for millions of years, preserving the extraordinary and ancient characteristics of its inhabitants.
Keywords: Sea in motion pictures